Mechanism and application of immune interventions in intracerebral haemorrhage - Xiaoxiao Xu; Yuanwei Li; Shiling Chen; Xuan Wu; Jiarui Li; Gaigai Li; Zhouping Tang (Expert Reviews in Molecular Medicine)
Despite stroke being one of the major and increasing burdens to global health, therapeutic interventions in intracerebral haemorrhage (ICH) continue to be a challenge. Existing treatment methods, such as surgery and conservative treatment have shown limited efficacy in improving the prognosis of ICH. However, more and more studies show that exploring the specific process of immune response after ICH and taking corresponding immunotherapy may have a definite significance to improve the prognosis of cerebral haemorrhage. Therefore, immune interventions are currently under consideration as therapeutic interventions in the ICH. In this review, we aim to clarify unique immunological features of stroke, and consider the evidence for immune interventions. In acute ICH, activation of glial cells and cell death products trigger an inflammatory cascade that damages vessels and the parenchyma within minutes to hours of the haemorrhage. Immune interventions that ameliorate brain inflammation, vascular permeability and tissue oedema should be administered promptly to reduce acute immune destruction and avoid subsequent immunosuppression. A deeper understanding of the immune mechanisms involved in ICH is likely to lead to successful immune interventions.